A comprehensive compensation method for piezoresistive pressure sensor based on surface fitting and improved grey wolf algorithm - Zhao, Xueliang; Chen, Ying; Wei, Guanghua; Pang, LiLi; Xu, Chongxuan (Measurement : journal of the International Measurement Confederation, 2023)
•The nonlinear and temperature drift characteristics for silicon piezoresistive pressure sensor are tested and analyzed.•The adjustable nonlinearity convergence factor, the weight vector and weight adjustment coefficient are proposed and established.•The comprehensive compensation method based on surface fitting and improved grey wolf algorithm is established.•The full range is better than 0.03 %, and the local range is less than 0.02 % with reducing fitting data.•The proposed method is easy to be used for piezoresistive pressure sensor without adding the additional hardware and software code. The optimized surface fitting method base on improved gray wolf algorithm (IGWO) is proposed to overcome the nonlinearity and temperature drift of piezoresistive pressure sensor. To improve the convergence rate and search ability of gray wolf optimization algorithm (GWO), the adjustable nonlinearity convergence factor is established. The weight vector and weight adjustment coefficient are integrated into the residual function of the least square method. Employing the maximum full range error as the fitness function, the least square method is continuously optimized by IGWO to establish the high-performance comprehensive compensation mathematical formula. The simulation and practical test results indicate that the maximum full-scale error in the full range is better than 0.03 %, and the maximum full-scale error in the local range is less than 0.02 % especially. The proposed method proposed method is very suitable for the application and production of industrial pressure sensor with many advantages.